Sports metaverses: theory and practice - Skarzhinskaya E.N. ,; Ermakov A.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the current state of the problem of developing a sports metaverse in the digital space based on a theoretical analysis of information sources, as well as cases of holding sporting events in metaverses. Methods and structure of the study. Scientific work was carried out during 2021-2024. and included a set of methods for collecting information (analysis of literary sources and content analysis of specialized Internet resources; conversations with heads of IT companies; participant observation at competitions in digital sports; testing of domestic VR games; participation in thematic scientific conferences of various levels and etc.). Results and conclusions. Based on the analysis, the authors propose the creation of sports metauniverses, which, based on artificial intelligence technologies, allow us to customize the choice of sport and the process of sports training, depending on the level of individual preparedness. In the future, the user himself can create sports and physical activities based on his own preferences with consulting support from the platform, as well as the possibility of implementation using current technologies.